The bad birthday idea - Valentine, Madeline (Alfred A. Knopf Books for Young Readers, 2013)
Ben refuses to play with his sister, Alice, because he likes robots and she likes dolls but when her birthday wish is for a robot that Ben really wants, he opens it first, accidentally breaks it, then tries to cover up his deed.